2019
DOI: 10.1111/ctr.13643
|View full text |Cite
|
Sign up to set email alerts
|

Tests for latent tuberculosis in candidates for solid organ transplantation: A systematic review and meta‐analysis

Abstract: Reactivation of latent tuberculosis following solid organ transplantation has serious consequences for the recipient. The most useful diagnostic test for latent TB is not clear. We conducted a systematic review and meta-analysis to assess the relative test performance of interferon gamma release assays (IGRAs) and the tuberculin skin test (TST) in people undergoing solid organ transplantation. The clinical or radiological risk factors were used as the proxy reference standard. Test performance was expressed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Most international guidelines recommend screening for LTBI in all kinds of SOT candidates/donors, and both the TST and IGRAs are recommended as screening tools. Different studies showed great differences in the diagnostic value of the TST and IGRAs, which may be due to different immunosuppressive states caused by various organ failures [ 79 ]. A study showed that the sensitivity of the TST was surprisingly low in this population, with only 20–25% of post-transplant ATBI cases having a positive response to the TST before SOT [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most international guidelines recommend screening for LTBI in all kinds of SOT candidates/donors, and both the TST and IGRAs are recommended as screening tools. Different studies showed great differences in the diagnostic value of the TST and IGRAs, which may be due to different immunosuppressive states caused by various organ failures [ 79 ]. A study showed that the sensitivity of the TST was surprisingly low in this population, with only 20–25% of post-transplant ATBI cases having a positive response to the TST before SOT [ 80 ].…”
Section: Discussionmentioning
confidence: 99%